1981
DOI: 10.1029/jb086ib10p09357
|View full text |Cite
|
Sign up to set email alerts
|

Focal depths and moment tensor representations of shallow earthquakes associated with the Great Sumba Earthquake

Abstract: Focal depths in the range 8 to 24 km below the seafloor were determined for seven of the larger shocks associated with the Great Sumba earthquake of August 19, 1977. Depth control was achieved by modeling digitized long‐period P waves recorded by the World‐Wide Standard Seismic Network. If the base of the rupture at the time of the mainshock were no greater than the depth of the deepest aftershock, the stress drop would be nearly 500 bars. Amplitude and first motion data from the P waves were inverted for poin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 41 publications
1
26
0
Order By: Relevance
“…In contrast, SILVER and JORDAN (1983) obtained a centroid depth shallower than 20 km from the moment spectra. Consistent with this centroid depth, FITCH et al (1981) found that the depth range of major aftershocks is 8-24 km and LYNNES andLAY (1988) obtained the source extent not deeper than 35 km from the analysis of long-period body waves.…”
Section: The 1933 Sanriku Earthquakesupporting
confidence: 62%
See 1 more Smart Citation
“…In contrast, SILVER and JORDAN (1983) obtained a centroid depth shallower than 20 km from the moment spectra. Consistent with this centroid depth, FITCH et al (1981) found that the depth range of major aftershocks is 8-24 km and LYNNES andLAY (1988) obtained the source extent not deeper than 35 km from the analysis of long-period body waves.…”
Section: The 1933 Sanriku Earthquakesupporting
confidence: 62%
“…The incorrect depths may lead to incorrect calculation of the take-off angles to local stations and thus result in incorrect fault plane solutions (SENO and KROEGER, 1983). Therefore, previous studies of trench-outer rise events (HERMANN, 1976;CHEN and FORSYTH, 1978;FITCH et al, 1981;STEIN et al, 1982;FORSYTH, 1982;CHINN and ISACKS, 1983;WARD, 1983;CHRISTENSEN and RUFF, 1987) have emphasized that these events must be studied individually using waveform analysis. In this study, we determined focal depths and fault plane solutions by comparison of synthetic and observed seismograms of WWSSN long-and short-period P waves.…”
Section: Introductionmentioning
confidence: 99%
“…This misestimation of the depth and source time function is systematically reflected as a strong correlation between the elements of the isotropic component, and among these elements M,, appears to be particularly poorly solved in surface-wave inversions, especially at shallow depths. This formalizes the trade-offs observed empirically between the isotropic part, the hypocentral depth and the source time function (Fitch et al 1981;Stein & Wiens 1986). It also indicates that, when an additional constraint must be applied in order to reduce the number of unknowns from six to five, choosing a constraint on the isotropic part, and particularly the condition M,, = -M x x -My,, is among the best possible choices.…”
Section: Correlations and Trade-offsmentioning
confidence: 95%
“…Moment tensor inversion has become an important and active domain in the physics of seismic source. In order to obtain some information, such as the source time function describing source rupture process, to determine the moment tensor describing the focal mechanism, and to estimate the scalar moment measuring the earthquake magnitude, seismologists have applied the moment tensor inversion to various data, such as the free oscillation (Gilbert, Dziewonski, 1975), surface wave (McCowan, 1976;Mendiguren, 1977;Aki, Patton, 1978;Kanamori, Given, 1981;Romanowicz, 1982;Lay, et al, 1982), body wave (Stump, Johnson, 1977;Ward, 1980;Fitch, et al, 1981;Dziewonski, et al, 1981) and near-source recording (Stump, Johnson, 1984;Ni, et al, 1991, Wu, etal, 1994 ~.…”
Section: Moment Tensor Inversionmentioning
confidence: 99%